Co-ordination of generalist care for patients towards the end of life: a literature review. (1st April 2011) - Mason, B L; Barclay, S; Dale, J; Daveson, B; Donaldson, A; Epiphaniou, E; Harding, R; Higginson, I J; Munday, D; Nanton, V; Shipman, C; Murray, S A
Abstract : Abstract: Introduction and aim: Increased coordination and collaboration have been highlighted as improving the provision of health and social care for people at the end of life. We aimed to review the literature concerning coordination or collaboration of care to determine whether coordination and collaboration improves the quality of care delivered by generalists towards the end of life. Methods: Searches in PUBMED and ISI Web of Knowledge for the stems 'coordinat-' or 'collaborat-' in the context of the stem 'palliat-' or the phrase 'terminal care.' Search of Web of Knowledge for the categories 'generalist health care' and 'palliative.' Search of PUBMED MeSH terms 'palliative care admin and organisation', 'terminal care admin and organisation' and 'Cooperative Behavior.' Electronic searches were supplemented by hand searches of leading palliative care journals (2008–2010). Results: 1672 articles initially identified as requiring further screening, and 55 eligible studies identified. Different approaches/terminology to enabling coordination and collaboration were identified including networks, integrated care pathways, partnerships, frameworks, programmes and 'collaboratives'. Lack of coordination and/or collaboration was routinely identified as a barrier to good palliative care. Conclusion: Approaches to enabling coordination and collaboration are evident in the literature but no metrics to measure coordination or collaboration were uncovered so it is impossible to determine whether a particular intervention increased coordination or collaboration. Therefore more research to determine whether collaboration and coordination improves quality of care is needed. Management or organisational theory as well as robust evaluation of models of co-ordination is indicated to guide current policy developments. This will require increased conceptual clarity regarding the terms collaboration and coordination in this context.